Immobilization of bacterial mixture of Klebsiella variicola FH-1 and Arthrobacter sp. NJ-1 enhances the bioremediation of atrazine-polluted soil environments - Pan, Zequn; Wu, Yulin; Zhai, Qianhang; Tang, Yanan; Liu, Xuewei; Xu, Xuanwei; Liang, Shuang; Zhang, Hao (Frontiers in Microbiology, 2023)
In this study, the effects of the immobilized bacterial mixture (IM-FN) of Arthrobacter sp. NJ-1 and Klebsiella variicola strain FH-1 using sodium alginate-CaCl2 on the degradation of atrazine were investigated. The results showed that the optimal ratio of three types of carrier materials (i.e., rice straw powder, rice husk, and wheat bran) was 1:1:1 with the highest adsorption capacity for atrazine (i.e., 3774.47 mg/kg) obtained at 30 ℃. On day 9, the degradation efficiency of atrazine (50 mg/L) reached 98.23% with cell concentration of 1.6 × 10⁸ cfu/mL at pH 9 and 30 ℃. The Box-Behnken method was used to further optimize the culture conditions for the degradation of atrazine by the immobilized bacterial mixture. The IM-FN could be reused for 2~3 times with the degradation efficiency of atrazine maintained at 73.0% after being stored for 80 days at 25 ℃. The population dynamics of IM-FN was explored with the total soil DNA samples specifically analyzed by real-time PCR. In 7 days, the copy numbers of both PydC and estD genes in the IM-FN were significantly higher than those of bacterial suspensions in the soil. Compared with bacterial suspensions, the IM-FN significantly accelerated the degradation of atrazine (20 mg/kg) in soil with the half-life shortened from 19.80 days to 7.96 days. The plant heights of two atrazine-sensitive crops (wheat and soybean) were increased by 14.99% and 64.74%, respectively, in the soil restored by immobilized bacterial mixture, indicating that the IM-FN significantly reduced the phytotoxicity of atrazine on the plants. Our study evidently demonstrated that the IM-FN could significantly increase the degradation of atrazine, providing a potentially effective bioremediation technique for the treatment of atrazine polluted soil environment and providing experimental support for the wide application of immobilized microorganism technology in agriculture.